(untitled) (Bioagro, 2020)
An acute test of toxicity was performed with seedlings Mauritia flexuosa exposed to contaminated soils in concentrations of 0, 4, 8, 16, 32 y 64 % of heavy crude oil under greenhouse conditions. Concentrations of up to 16 % did not significantly affect the survival of seedlings, while at the maximum concentration of 64 % did not survive any seedling. In correlation with survival, stem biomass and total biomass did not decreased until a concentration of heavy oil of 16 %, while root biomass and shoot/root ratio showed no differences between concentrations where seedlings survived. The results show a high tolerance M. flexuosa to soil contamination with heavy crude oil and its potential to reforest contaminated soils with such type of hydrocarbon.